SYTL3–SLC22A3 Single-Nucleotide Polymorphisms and Gene–Gene/Environment Interactions on the Risk of Hyperlipidemia - Zheng, Peng-Fei; Yin, Rui-Xing; Cao, Xiao-Li; Guan, Yao-Zong; Deng, Guo-Xiong; Wei, Bi-Liu; Liu, Chun-Xiao (Frontiers in Genetics, 2021)
The current study aims to further delineate the associations between the synaptotagmin-like 3 (SYTL3) and solute carrier family 22 member 3 (SLC22A3) single-nucleotide polymorphisms (SNPs) and their haplotypes and gene–gene (G × G)/environment (G × E) interactions on the risk of hyperlipidemia (HLP) in the Maonan and Han ethnic groups. Genotype distribution among the SYTL3–SLC22A3 SNPs in 2,829 individual patients bearing no relationship to each other (Han, 1,436; Maonan, 1,393) was analyzed utilizing next-generation sequencing techniques. The genotype frequencies of the rs6455600, rs2129209, and rs446809 SNPs were varied between the two ethnic groups (P < 0.05–0.001). Various SNPs were correlated with serum levels of triglyceride (TG; rs446809), total cholesterol (TC; rs6455600, rs2129209, and rs539298), and low-density lipoprotein cholesterol (LDL-C; rs446809) among the Han population, whereas various SNPs were also correlated with TC (rs6455600 and rs539298), TG (rs446809), and LDL-C (rs446809) levels in the Maonan ethnic group (P < 0.008–0.001). One part of haplotypes resulted in worsened HLP-related morbidity in the Han (SYTL3 A-C-A-A; SLC22A3 A-A and A-G; and SYTL3–SLC22A3 A-C-A-A-A-A and A-C-A-A-A-G) and Maonan (SYTL3 A-C-A-A; SLC22A3 A-A and A-G; and SYTL3–SLC22A3 A-C-A-A-A-A, G-T-C-A-A-A, and G-T-C-A-C-A) ethnic groups, whereas another part of haplotypes lowered HLP-related health risks in the Han (SLC22A3 C-A and C-G and SYTL3–SLC22A3 A-C-A-A-C-A, A-C-A-A-C-G, and G-T-C-A-C-A) and Maonan (SLC22A3 C-G and SYTL3–SLC22A3 A-C-A-A-C-G) ethnic groups. We discovered that the SYTL3–SLC22A3 SNPs and their haplotypes were associated with serum lipid levels and the risk of HLP in our studied populations.